A Numerical computation of non-dimensional form of a mathematical model of soil salinity profile in a rice field near marine shrimp aquaculture farm - Pongnoo, Nattawoot; Pochai, Nopparat (My University, 2011)
The high level salinity of soil is a main problem of a plant grows less in rice field near marine shrimp aquaculture farm. The electrical conductivity of soil is an indicator of soil salinity assessment. The methods to detect the amount of salinity of soil are field measurement and mathematical simulation. In this paper, the direct current model of electric conductivity of soil is used. The Lax-Wendroff method is used to approximate the conductivity of soil in the area near marine shrimp aquaculture farm.
Keywords: Direct current method; Electric conductivity; Lax-Wendroff method; Marine shrimp aquaculture farm; Salinity